Oligarchic planetesimal accretion and giant planet formation II - Fortier, Andrea (2009)
Aims. The equation of state calculated by Saumon and collaborators has been adopted in most core-accretion simulations of giant-planet formation performed to date. Since some minor errors have been found in their original paper, we present revised simulations of giant-planet formation that considers a corrected equation of state. Methods. We employ the same code as Fortier and collaborators in repeating our previous simulations of the formation of Jupiter. Results. Although the general conclusions of Fortier and collaborators remain valid, we obtain significantly lower core masses and shorter formation times in all cases considered. Conclusions. The minor errors in the previously published equation of state have been shown to affect directly the adiabatic gradient and the specific heat, causing an overestimation of both the core masses and formation times.